Penetapan Subject Matter Geografi Melalui Pengamatan Terbatas Fenomena Geosfer pada Pembelajaran di Rumpun IPS SMA - Farkhan, Muhammad Robith; Maryani, Enok (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Geography learning at high school level which is studied in the social sciences group examines various kinds of geosphere phenomena as supports for human life, through a spatial approach, environmental approach and regional approach. The purpose of this research is to determine the determination of geographic subject matter through observing geosphere phenomena in learning in social studies classes at SMA. This research method uses literature studies which contain various literature sources, namely accredited journals, proceedings, books and relevant sources that are trusted and scientific. The research results showed that the determination of geography subject matter must be adjusted to the syllabus as a curriculum standards for geography subjects in SMA. The geosphere phenomenon is not only a theoretical concept in books but can be observed directly, simply through the environment around the school. The activity of observing geosphere phenomena around students is a source of geography learning, a complement to the theory presented in the textbook. It is concluded that geography learning can be implemented through theory and practice of observing geosphere phenomena. The contribution of this research to social studies learning lies in the diversity of social studies learning sources which include humans and all their life support.